Complementary and alternative medicine for the treatment and diagnosis of asthma and allergic diseases - Passalacqua, G.; Compalati, E.; Schiappoli, M.; Senna, G. (Monaldi Archives for Chest Disease, 2005)
The use of Complementary/Alternative Medicines (CAM) is largely diffused and constantly increasing, especially in the field of allergic diseases and asthma. Homeopathy, acupuncture and phytotherapy are the most frequently utilised treatments, whereas complementary diagnostic techniques are mainly used in the field of food allergy- intolerance. Looking at the literature, the majority of clinical trials with CAMS are of low methodological quality, thus difficult to interpret. There are very few studies performed in a rigorously controlled fashion, and those studies provided inconclusive results. In asthma, none of the CAM have thus far been proved more effective than placebo or equally effective as standard treatments. Some herbal products, containing active principles, have displayed some clinical effect, but the herbal remedies are usually not standardised and not quantified, thus carry the risk of toxic effects or interactions. None of the alternative diagnostic techniques (electrodermal testing, kinesiology, leukocytotoxic test, iridology, hair analysis) have been proved able to distinguish between healthy and allergic subjects or to diagnose sensitizations. Therefore these tests must not be used, since they can lead to delayed or incorrect diagnosis and therapy.